2018
DOI: 10.15866/irece.v9i1.13737
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Potential of Sandy Soil from Small Laboratory Machine Foundation Model

Abstract: Liquefaction is a phenomenon that occurs during earthquakes, and leads to ground failure. Water-saturated, well sorted, fine grain sands and silts behave as viscous fluid as a result of liquefaction. This behavior of fluids is very different than solids behavior. This paper presents and discusses the results of 54 experimental model tests, all of them were performed on saturated sand under vertical dynamic traffic load using different relative densities (medium and dense), different shapes of footing (square a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Loose sand contains large voids which can easily compact and increase the settlement. Similar findings by Fattah et al [18] illustrated that the value of foundation settlement increases with increasing load amplitude.…”
Section: The Settlement Of Machine Foundationsupporting
confidence: 86%
See 1 more Smart Citation
“…Loose sand contains large voids which can easily compact and increase the settlement. Similar findings by Fattah et al [18] illustrated that the value of foundation settlement increases with increasing load amplitude.…”
Section: The Settlement Of Machine Foundationsupporting
confidence: 86%
“…Bhatia [17] showed the permissible limits of amplitude for different machines for different frequencies and the frequency classified as low-speed machines (100-1500 rpm), medium-speed machines (1500-3000) rpm and high-speed machines (3000-10000) rpm and above. Fattah et al [18] showed that the settlement of a square foundation in medium sand was affected by the embedment.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that as load amplitude and frequency were increased, defor mation and liquefaction occurred more frequently and more severely. An experimental work for the liquefaction of sandy soil under the influence of a small machine model has been conducted [3]. The research has concentrated on varying the relative density for the sand, the shape and embedment of the footing model.…”
Section: Introductionmentioning
confidence: 99%